2020
DOI: 10.34172/ajmb.2020.11
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Anti-apoptotic Effects of Peganum harmala Leaf Extract on Type 2 Diabetes in the Kidney of Male Wistar Rats

Abstract: Background: Growing evidence has shown that the apoptosis of cells plays an important role in the advancement of the Diabetic nephropathy (DN). Objectives: This study attempted to discover the therapeutic potential of Peganum harmala leaf extract in the apoptosis of diabetic kidney disease. Methods: In the present experimental research, 32 male Wistar rats were studied, and diabetes was induced by streptozotocin (STZ) (65 mg/kg). The animals were randomly divided into four groups (n=8, in each group) as follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…Moreover, it diminishes the formation of thiobarbituric acid reactive substances (TBARS) in the brainby inhibiting acetylcholinesterase and consequently enhancing glutathione levels (35). As a result, our research supports P. harmala's role by demonstrating pharmacological apoptosis inhibition in diabetics subjects, which is consistent with other studies (19,20). Bax gene expression in the D group, including rats with diabetes, was highly significant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, it diminishes the formation of thiobarbituric acid reactive substances (TBARS) in the brainby inhibiting acetylcholinesterase and consequently enhancing glutathione levels (35). As a result, our research supports P. harmala's role by demonstrating pharmacological apoptosis inhibition in diabetics subjects, which is consistent with other studies (19,20). Bax gene expression in the D group, including rats with diabetes, was highly significant.…”
Section: Discussionsupporting
confidence: 91%
“…There are few studies on the anti-apoptotic effect of P. harmala seed extracts (18). Recently, Kajbaf et al have shown that the leaf extract of P. harmala cannot inhibit apoptosis by reducing caspase-3 expression in the diabetic kidney model (19). Also, it is demonstrated that the seed extract of P. harmala is more effective in controlling diabetes and apoptosis in the beta cells of the pancreas (20).…”
Section: Introductionmentioning
confidence: 99%